PREDIKTOR PENYESUAIAN DIRI DI SEKOLAH MENENGAH PERTAMA PADA REMAJA SEBAGAI SISWA BARU - Aryanti, Zusy (JURNAL TAPIS, 2013)
This study aims to determine empirically the role of emotion regulation, social competence and sexto predict self-adjustment at adolescent as the new student andwhat are difference between boy and girl. The subject was taken from 120 students of junior High School at Metro city by using cluster random sampling tecnique.Â  The instrument of this research are emotion regulation scale ,social competence scaleand adjustment scale based on Likert models. Analysis technique used is the Regression and ANOVA. The results showed 1), emotion regulation, social competence and sex can predictsself adjustment is 18.6 % .2) There are differences in elf adjustment and emotion regulation among boys and girls. 3) There is a positive relationship between emotion regulation with self adjustment, 4) There is a negative relationship between social competence with self adjustment.Keywords: Predictor, adaptation, teenager